Inverse Correlation Between Helicobacter pylori Colonization and Obesity in a Cohort of Inner City Children. Issue 1 (11th October 2014) - Vo, Hanh D.; Goli, Sridhar; Gill, Rupinder; Anderson, Virginia; Stefanov, Dimitre G.; Xu, Jiliu; Kulsum‐Mecci, Nazia; Schwarz, Steven M.; Rabinowitz, Simon S.
Abstract Background Recently, publications in adults and children have documented a potential role of Helicobacter pylori (H. pylori) in decreasing the likelihood of obesity. The present study compares the prevalence of H. pylori colonization between obese (body mass index [BMI] ≥ 95th percentile) and healthy weight (BMI ≥ 5th to <85th percentiles) children seen at an inner city medical center in the United States. Methods This retrospective study reviewed clinical features, BMI, and gastric histology of consecutive children aged 1–18 years undergoing an esophagogastroduodenoscopy. BMI percentile was calculated for age and gender. Helicobacter pylori colonization was determined by histopathologic identification of the organism. Multiple logistic regression was employed to measure the association between BMI and H. pylori colonization, controlling for baseline age, gender, and presenting symptoms. Results Among 340 patients (51.5% female, mean age of 10.5 ± 4.7 years), 98 (29%) were obese and 173 (51%) were healthy weight. The H. pylori colonization rate of the entire cohort was 18.5% (95% CI = 14.7–23.0%). Among obese children, 10% had H. pylori colonization compared to 21% of the healthy weight children (RR = 2.1, 95% CI = 1.1–4.0). Conversely, 39% of noncolonized children, but only 21% of the infected children, were obese (RR = 1.8, 95% CI = 1.1–3.3). Multivariate analysis revealed that being colonized with H. pylori is associated with a 50% reduction in the odds of being obese (adjusted OR = 0.5, 95% CI = 0.2–1.0). Conclusions Our findings in a North American cohort are in agreement with studies from Asia and Europe suggesting that H. pylori infection decreases the prevalence of obesity in children. Further work to characterize the extent and nature of this relationship is warranted.